Iot-integrated Smart Gardening System For Real-time Monitoring And User-controlled With Smart Film - Affa Rozana Abdul Rashid; M. K. A. Azmi; Wan Maisarah Mukhtar; Nur Athirah Mohd Taib (Penerbit Universiti Teknikal Malaysia Melaka, 2025)
Indexed by Scopus (Tier 3)